Continuum beliefs and mental illness stigma: A systematic review and meta-analysis of correlation and Intervention studies. (20th October 2021) - Peter, L-J; Schindler, S; Sander, C; Schmidt, S; Muehlan, H; McLaren, T; Tomczyk, S; Speerforck, S; Schomerus, G
Abstract: Promulgating a continuum model of mental health and mental illness has been proposed as a way to reduce stigma by decreasing notions of differentness. In a systematic review and meta-analysis, we examined whether continuum beliefs are associated with lower stigma, and whether continuum interventions reduce stigma. We searched three electronic databases (PubMed, Web of Science and PsycINFO) yielding 6726 studies. After screening, we included 33 studies covering continuum beliefs, mental illness and stigma. Of these, 13 studies were included in meta-analysis. Continuum beliefs are consistently associated with lower stigma. Interventions were effective in manipulating continuum beliefs but differ in their effects on stigmatizing attitudes. We discuss whether and to what extent attitudes towards people with mental illness can be improved by providing information on a mental health-mental illness continuum. It appeared to be relevant whether interventions promoted a feeling of "us" and a process of identification with the person with mental illness. We discuss implications for the design of future interventions using the example of our current online anti-stigma intervention, which was developed on the basis of these considerations, containing gamified elements with the purpose of identification and involvement.